2023
DOI: 10.1126/science.ade4970
|View full text |Cite
|
Sign up to set email alerts
|

An observed population of intermediate-mass helium stars that have been stripped in binaries

M. R. Drout,
Y. Götberg,
B. A. Ludwig
et al.

Abstract: The hydrogen-rich outer layers of massive stars can be removed by interactions with a binary companion. Theoretical models predict that this stripping produces a population of hot helium stars of ~2 to 8 solar masses ( M ☉ ), however, only one such system has been identified thus far. We used ultraviolet photometry to identify potential stripped helium stars then investigated 25 of them using optical spectroscopy. We identified stars with high temperatures (~60,000 to 100,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…This issue could be mitigated by using BPASS spectral synthesis (Eldridge et al 2017) as the BPASS SSP at this age and metallicity produces a stronger UV emission at the fixed Q H . However, we caution that there is significant uncertainty in the ionizing and UV fluxes of massive metal-poor stars (e.g., Olivier et al 2022;Umeda et al 2022;Drout et al 2023). In the next section, we propose a solution that does not require >80% dominance by nebular emission.…”
Section: Inferred Ionizing Spectramentioning
confidence: 97%
“…This issue could be mitigated by using BPASS spectral synthesis (Eldridge et al 2017) as the BPASS SSP at this age and metallicity produces a stronger UV emission at the fixed Q H . However, we caution that there is significant uncertainty in the ionizing and UV fluxes of massive metal-poor stars (e.g., Olivier et al 2022;Umeda et al 2022;Drout et al 2023). In the next section, we propose a solution that does not require >80% dominance by nebular emission.…”
Section: Inferred Ionizing Spectramentioning
confidence: 97%
“…A similar problem is also seen in z ∼ 2-4 He II emitters (Nanayakkara et al 2019;Saxena et al 2020), where the He II equivalent widths are usually underpredicted by the BPASS models (Xiao et al 2018) with more realistic metallicities (Z = 0.005, 0.1, 1 Z e ). Consequently, additional ionizing sources, such as Wolf-Rayet stars and stripped helium stars (Drout et al 2023), might still be needed to reproduce the observed line strengths.…”
Section: Uv Line Diagnosticsmentioning
confidence: 99%
“…The resulting stripped star first contracts as a hot helium star. Drout et al (2023) and Götberg et al (2023) recently presented the discovery and analysis of such stars, which so far had been missing.…”
Section: Introductionmentioning
confidence: 99%